2020
DOI: 10.3389/fmars.2020.00275
|View full text |Cite
|
Sign up to set email alerts
|

Deriving a Proxy for Iron Limitation From Chlorophyll Fluorescence on Buoyancy Gliders

Abstract: Chlorophyll fluorescence, primarily used to derive phytoplankton biomass, has long been an underutilized source of information on phytoplankton physiology. Diel fluctuations in chlorophyll fluorescence are affected by both photosynthetic efficiency and nonphotochemical quenching (NPQ), where NPQ is a decrease in fluorescence through the dissipation of excess energy as heat. NPQ variability is linked to iron and light availability, and has the potential to provide important diagnostic information on phytoplankt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…We also observe a significant positive relationship between F/Chl and NPQ max (second‐ranked candidate predictor; Table S3 in Supporting Information ). While NPQ max has not conclusively been shown to be a proxy for Fe limitation, Ryan‐Keogh and Thomalla (2020) showed similar patterns in NPQ max and α NPQ when glider and CTD data from different seasons (with different levels of Fe limitation) were analyzed. Likewise, these two variables are correlated in our BGC‐Argo dataset (conditional r 2 = 0.44, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observe a significant positive relationship between F/Chl and NPQ max (second‐ranked candidate predictor; Table S3 in Supporting Information ). While NPQ max has not conclusively been shown to be a proxy for Fe limitation, Ryan‐Keogh and Thomalla (2020) showed similar patterns in NPQ max and α NPQ when glider and CTD data from different seasons (with different levels of Fe limitation) were analyzed. Likewise, these two variables are correlated in our BGC‐Argo dataset (conditional r 2 = 0.44, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The NPQ‐corrected fluorescence was used to estimate average fluorescence between 10 and 40 dbar ( F mean ), which could then be related to the average Chl Kd over the same depths, yielding F/Chl. Additionally, NPQ‐corrected fluorescence was used to estimate a proxy for Fe limitation of the phytoplankton, following the approach by Ryan‐Keogh and Thomalla (2020). Building on earlier work relating NPQ and the Fe limitation status of phytoplankton (Schallenberg et al., 2020; Schuback & Tortell, 2019; Schuback et al., 2015), these authors found that the initial slope of the NPQ‐PAR relationship (α NPQ ) was an indicator of Fe limitation.…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, this approach to fluorescence has the potential to be applied to data from autonomous floats in the Southern Ocean, such as the biogeochemical (BGC) Argo fleet. A recent application to glider data from the SAZ in the Atlantic Ocean has allowed identification of regions and time periods where Fe limitation was relieved (Ryan-Keogh and Thomalla, 2020). Studies of this kind will improve our understanding of biogeochemical cycles in the understudied Southern Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the absorption cross-section of PSII photochemistry (σ PII ) often increases under iron-limiting conditions, necessitating rapidly inducible NPQ under fluctuating light availability (e.g., Schuback and Tortell, 2019). Increased NPQ levels under iron-limited conditions can be extrapolated to observations of diurnal quenching of ChlF from "standard" in-vivo ChlF fluorometers deployed in continuous flow through and in-situ systems (Roesler and Barnard, 2013;Ryan-Keogh and Thomalla, 2020;Schallenberg et al, 2020).…”
Section: Exploring Environmental Controls On Primary Productivitymentioning
confidence: 99%